Localising Informal Practices in Transnational Entrepreneurship - Sandoz, Laure (My University, 2021)
In recent academic literature, transnational migrant entrepreneurs tend to be represented as active agents capable of mobilising resources situated in different countries to develop new businesses. Mobility, however, is an unequally distributed resource, and restrictive migration regimes limit the possibilities of individuals to become entrepreneurs. This article focuses on the role of informal practices in the business strategies of migrants who develop their activities across national borders. Based on ethnographic research in Barcelona, Spain, it argues that, in a context of unequal access to formal resources, resorting to informality is crucial for many entrepreneurs as it enables them to expand their options for social mobility and achieve personal goals that would otherwise remain unreachable. At the same time, the article proposes a critical perspective on the notions of informality and entrepreneurship. It highlights that these concepts rely on context-dependent norms set by certain social groups and challenged by others, which influence who can become an entrepreneur in specific environments. While certain categories of migrants are favourably positioned with regard to these norms, others are hindered by them and therefore are forced to engage in alternative entrepreneurial activities. How this is achieved and the costs involved depend on the entrepreneur’s capacity to mobilise economic, cultural, social, and moral resources as well as on the perception of their practices as more or less legitimate or socially acceptable.
Keywords: Entrepreneurship; Transnationalism; Migrant businesses; Informality; Critical ethnography